2004
DOI: 10.1097/00001503-200406000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Living-related liver transplantation: implication for the anaesthetist

Abstract: In this paper we review and summarize the potential impact of findings and advances made in this particular field as described by the most important articles published during the past year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…With advances in surgical techniques and perioperative management, mortality and morbidity after liver donation have decreased dramatically 8 . Therefore, ensuring donor safety while providing satisfactory pain control has become an important outcome, however, it can be challenging for anesthesiologists in transplantation centers 1 . Previous studies have shown that postoperative pain in living liver donors persists for up to 1‐year after donation 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With advances in surgical techniques and perioperative management, mortality and morbidity after liver donation have decreased dramatically 8 . Therefore, ensuring donor safety while providing satisfactory pain control has become an important outcome, however, it can be challenging for anesthesiologists in transplantation centers 1 . Previous studies have shown that postoperative pain in living liver donors persists for up to 1‐year after donation 16 .…”
Section: Discussionmentioning
confidence: 99%
“…8 Therefore, ensuring donor safety while providing satisfactory pain control has become an important outcome, however, it can be challenging for anesthesiologists in transplantation centers. 1 Previous studies have shown that postoperative pain in living liver donors persists for up to 1-year after donation. 16 Specifically, Holtzman et al 16 and the Adult-to-Adult Living Donor Liver Transplantation study group 17 reported that 21% 17 and 42%-74% 16 of living donors experienced moderate or severe acute postoperative pain, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Once a suitable donor is available, LDLT can be performed, thus shortening the waiting period and eliminating potential death among the patients in the waiting list. 31 The quality of the liver graft is good as it is procured from a healthy donor with stable hemodynamics without needing inotropic drugs for support during the organ procurement, and it has very short cold ischemic time, thereby minimizing preservation injury. 32 Likewise, LDLT recipients are usually less sick and in better condition in comparison with deceased LT recipients; therefore, the outcome is similar to or even better than that of deceased LT recipients in terms of graft and patient survival.…”
Section: Beneficial Aspects Of Ldltmentioning
confidence: 99%
“…Over the years, advancements in surgical and perioperative management have significantly improved the outcomes of LDLT leading to a reduction in mortality and morbidity rates [1]. Despite these advancements, ensuring donor safety while providing adequate pain control remains a significant challenge for healthcare professionals in transplantation centers [2]. Previous studies have revealed that postoperative pain can persist for a considerable duration, with some living liver donors experiencing moderate to severe acute postoperative pain and a subset of individuals progressing to chronic pain [3][4][5].…”
Section: Introductionmentioning
confidence: 99%